An Integrated Study for Solving High Vibration Problem of A Deep Well Turbine Pump - El- Gazzar, Dalia M. (Journal of Advanced Industrial Technology and Application, 2023)
In this study, a deep well vertical turbine pump experienced extremely high vibrations for a long time although it still being new. It hasn’t been in operation for over 6 months. A novel strategy is implemented by using well-conceived techniques. The experimental modal analysis is confirmed a presence of a natural frequency. Modifications are carried out to overcome resonance. Finite element analysis is applied to determine the reed critical frequencies as a powerful tool to identify and mitigate vibration issues. On-site motor balancing is done to remove vibrations due to the residual imbalance. Results reveal decreasing vibration level by about 8% after solving all problems.